Implementation of Educational Supervision in Improving Learning Quality - Hidayat, Hidayat; Susanti, Ai Citra; Juwariah, Cucu; Astuti, Dini (International Journal Administration, Business & Organization, 2025)
This research aims to describe the implementation of the educational supervision program in improving the quality of learning at SMPN 1 Ibun, Bandung Regency, through the PDCA (Plan-Do-Check-Act) approach. The research approach used is qualitative with a qualitative descriptive method. Data collection techniques include observation, in-depth interviews, and documentation. The results show that the supervision program is implemented systematically through four stages: planning, execution, evaluation, and follow-up. The planning stage involves teachers in preparing schedules and supervision instruments. In the execution stage, supervision is conducted collaboratively through classroom observation and reflective discussions. Evaluation is based on learning data and teacher reflections, which are then followed by corrective actions in the form of training and mentoring. The entire PDCA-based supervision process has proven effective in improving teachers' competencies, the quality of learning, and a reflective culture in the school environment. Keywords: Educational Supervision, Learning Quality, PDCA, Teacher